Super Architects and dream factories - Pickersgill, Sean (Interstices: Journal of Architecture and Related Arts, 2016)
One of the most visible aspects of architectural education is the graduating project that conventionally summarises a student’s approach to architectural practice. While these projects have a responsibility to ensure their graduands have an explicit range of pragmatic skills, there are many projects that seek to explore ideas and formal propositions that go well beyond programme prescriptions. Many of these projects stretch the limits of fictionality and create speculative worlds that are genuinely novel in their synthesis of the competing opportunities within an expanded definition of what ‘architecture’ can be. This paper analyses some of the implications of this condition and undertakes a critical categorisation of the prevailing tendencies emerging with these project approaches by way of the website Super Architects.